Postcolonial Frameworks with Survivors’ Voices: Teaching about contemporary and historical forms of slavery and forced labour - Yea, Sallie (Anti-Trafficking Review, 2021)
Much of the information for educating students and the public about human trafficking only involves survivors’ direct experiences as brief excerpts from more complex and detailed narratives. In this paper, I draw on a postcolonial framework to argue that sidelining survivors’ voices can bolster anti-slavery stakeholders’ agendas by selectively using survivors’ narratives to illustrate narrow constructions of slavery and forced labour. As part of education and awareness efforts, such approaches to understanding slavery and forced labour also perpetuate stereotypes that trafficked persons are powerless and lack agency. Therefore, I present an alternative educational approach to remedy these tendencies by viewing and discussing narratives by, and about, trafficked persons. This paper uses a university-level humanities and social science subject on trafficking and slavery, and related assessment tasks, as a case study to demonstrate the potential of survivors’ voices in teaching about slavery.